MUCOCUTANEOUS MANIFESTATIONS OF CHIKUNGUNYA FEVER: A STUDY FROM AN EPIDEMIC IN COASTAL KARNATAKA - Bhat, Ramesh M (Medknow Publications, 2011)
BACKGROUND: Chikungunya fever (CF) epidemic has recently re-emerged in India affecting large population. Mucocutaneous manifestations are an important clinical feature of the disease. We have reviewed mucocutaneous manifestations of the disease during a recent epidemic in coastal Karnataka. PATIENTS AND METHODS: Seventy-five “suspect cases” of CF with dermatological manifestations were examined. RESULTS: We categorized the mucocutaneous manifestation into six groups: 1. skin rash, 2. apthae like ulcers, 3. pigmentary changes, 4. desquamation, 5. exacerbation of the existing dermatoses, 6. miscellaneous. Skin rashes were the most commonly observed skin changes followed by apthae like ulcers and pigmentary changes. Desquamation of the skin over the face is a new manifestation observed by us. CONCLUSION: wide spectrum of mucocutaneous manifestations is observed in CF. We have provided a classification for these manifestations, which may help in better recognition and uniform recording in future.